Interdisciplinary Perspectives on the Value of Massage Therapy in a Pediatric Hospice. Issue 4 (August 2019) - Egeli, Deetria; Bainbridge, Lesley; Miller, Tanice; Potts, James
Abstract : Canuck Place Children's Hospice in Vancouver, Canada, has been hosting a massage therapy practicum within the hospice since 2011. The practicum is delivered by upper-level massage therapy students who are supervised by a registered massage therapist and clinical instructor through West Coast College of Massage Therapy. This study aimed to explore clinicians' perspectives on the value of providing massage therapy to support children in hospice care, their families, and staff. The research participants (n = 6) comprised Canuck Place clinicians who have experience with the massage therapy practicum. In this descriptive phenomenological inquiry, semistructured interviews and thematic analysis were used. The findings demonstrated that Canuck Place clinicians valued the massage therapy practicum for its practical support in terms of creating access to massage therapy and self-care in the hospice. Massage therapy was also valued for supporting physical wellness (injury prevention/maintenance and symptom management) and psychosocial wellness (supporting dignity, interconnection, intraconnection, and rest/relaxation and providing a source of comfort/nurturing). This study is the first to explore clinicians' perceptions of massage therapy within a pediatric hospice and contributes to understanding massage therapy's potential role in the support of children, families, and staff within a hospice setting.